Otimiza??o de tr?fego roteamento e crit?rios de prote??o com redes ?pticas - Pereira, Helder Alves (2002)
Nowadays, many researchers of optical networks concentrate their studies on how to achieve the implementation of all links in the network, by using only the optical domain. This concept allows the transmission, switching and reception of all optical signals without eletronic conversion, and at the same time, increases the transmission speeds and the corresponding capacity of the network. The main purpose of this work recalls a fundamental question that is: How to use efficient routing and protection methods to optimize the networks performance, their trustfulness and cost-benefit relation. For a better understanding of the subject of this dissertation, some of the most important theoretical concepts involving the optical networks will be presented here. All the simulations were carried out by using an efficient numerical platform, which is the VPItransportMaker? (VPIsystems Inc., Homdel, NJ, USA). This is the most important tool to realize all kinds of analysis done in this work. The software allows the analysis of the performance of an optical network configured with a wide variety of structured architectures merged in generic topologies. Furthermore, some original codes are generated by using another computer platform largely explored in the fields of the Eletrical Engineering, which is the MatLab (MathWorks USA).